Principal's Strategy in Implementing Educational Management at SMA Bina Warga 1 Palembang - Retno Anggrayni; Syarwani Ahmad; Nuril Furkan (International Journal of Studies in International Education, 2025)
The principal is the highest leader in an educational unit who has the task and responsibility to manage the educational unit, therefore this study aims to describe and analyze the Principal's strategy in implementing educational management and the factors that hinder and support the implementation of the Principal's strategy in implementing educational management and the efforts made by the Principal in overcoming obstacles in the implementation of Educational Management at SMA Bina Warga 1 Palembang. The research data were obtained by interviews, observation and document methods which were analyzed using interactive model analysis. Based on the results of the study, it was concluded that 1) the Principal's strategy in implementing educational management at SMA Bina Warga 1 Palembang implemented the principles and functions of educational management such as planning, organizing, implementing/driving, and supervising, especially in the governance of students, educators and education personnel, and facilities and infrastructure so that the implementation of education runs in accordance with applicable regulations. 2) inhibiting and supporting factors for the implementation of the principal's strategy in implementing educational management at SMA Bina Warga 1 Palembang including the principal's ability in educational management and leadership, support and active participation of educators and educational personnel, availability of adequate facilities and sufficient resources to support the learning process, a positive culture that has grown and developed in the school. While inhibiting factors include budget limitations, less than optimal communication and coordination, educators' understanding of new approaches to changing school conditions, and parental support that is not yet complete. 3) efforts made to overcome obstacles to the principal's strategy in implementing educational management at SMA Bina Warga 1 Palembang include optimizing the use of human resources, a persuasive approach to teachers and stakeholders, implementing time management, strengthening collaboration with parents and other stakeholders